Changes in Respiratory Function in Asthma Patients using Respiratory Inspiration Muscle Exercise: Literature Review - Syaifuddin Kurnianto; Anggia Astuti; Raden Endro Sulistyono; Maharani Cahyo Putri (Nursing and Health Sciences Journal (NHSJ), 2022)
Asthma is characterized by narrowing and inflammation of the bronchi, with symptoms of dyspnea, fatigue, and limited activity. This study aims to explain the effect of respiratory inspiratory muscle training on changes in respiratory function based on the results of previous studies. This study was compiled based on a literature review that came from the databases: PubMed, springer link, and google scholar which were selected based on the inclusion criteria that have been set. From 272 articles found, only 6 articles deserve to be reviewed. The results of the review stated that respiratory inspiratory muscle exercise had an effect on changes in respiratory function in asthmatic patients with a very significant significance value. Changes provided by inspiratory muscle training are related to respiratory muscle strengthening which reduces respiratory stimulus and ventilation requirements for a given workload, contributing to more efficient breathing patterns and decreased perception of dyspnea. Inspiratory respiratory muscle exercise, either done alone or in combination with other respiratory rehabilitation programs, can increase the strength of the respiratory muscles so as to have an improved impact on the respiratory function of children with asthma from children to adults.